SYSTEM FILTRASI DAN STERILISASI ULTRA VIOLET (UV) PADA PEMELIHARAAN ABALONE (Holiotis tokobushi / squamata) - Wiwi soemardjati; Abdul Muqsith (Faculty of Science and Technology University Ibrahimy, 2013)
This study was conducted from April to October 2011, aims to determine the effectiveness of the use of filtration and sterilization system (UV) on maintenance media abalone (Holiotis tokobushi / Squamata). The research objectives is to increase survival rate of stem abalone (Holiotis tokobushi / Squamata) more than 75%. The results showed that the maintenance of stem abalone better by using media that has been filtered sea water and in the Ultra Violet (UV). The use of UV to reduce the total bacteria of 6x104 CFU/ml to 4x103 CFU/ml. Total vibrio green colony of 1 x 101 CFU/ml to 0 CFU/ml and total vibrio yellow of 6x101 CFU/ml to 2x101 CFU/ml. Survival Rate aircraft maintenance abalone using filtration and UV amounted to 90.4%. The growth rate of the parent abalone during the study average of 4.10 ± 1.07 mg / month. Need to improve the nutrition / nutrients to feed abalone and seaweed species variation and the need for further research about the use of low temperature for spawning maintenance and abalone.